Schedule of Activities and Programs (Symphony in the Flint Hills, 2015)
The schedule of activities and program notes, including information on conductor Aram Demirjian and the Kansas City Symphony, guest artist Lyle Lovett, Heritage Culture Presentations, Prairie Art, and Prairie Photography.
Keywords: Kansas City Symphony; Symphony in the Flint Hills; Heritage Culture; art; photography; pictures; images; Lyle Lovett; Aram Demirjian